PERILAKU BERWISATA WISATAWAN NUSANTARA PASCA PANDEMI COVID-19 - Rahmattullah Harianja; Rifki Rahmanda Putra; Asep Nurul Ajiid Mustofa; Mentari Pratami; Andi Syahputra; Surya Tri Esthi Wira Hutama (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2022)
In West Java, domestic tourist visits in the past year have decreased by around 42,1% from 2019 to 2020. This is inseparable from the direct impact of the pandemic on the tourism sector. The purpose of this study was to analyze the travel behavior of domestic tourists after the Covid-19 pandemic in West Java. This study uses a descriptive approach with the primary data needed in this study, namely data on tourist characteristics and facts regarding domestic tourist behavior. Data was collected by distributing questionnaires to 200 respondents who were domestic tourists who had visited regency/cities in West Java in the last two years. The data were processed by statistical descriptive analysis techniques. The characteristics of tourists in this study are described in several aspects, namely demographic aspects, occupational aspects, gender aspects, and educational aspects, and also described tourist activities in several phases (namely the dreaming phase, planning phase, booking phase, experience phase and sharing phase). The pattern of travel behavior of domestic tourists in West Java concerning post-pandemic tourism shows a trend that tourists who are millennials and zillennials are very concerned about cleanliness, health, and security. Tourism stakeholders in West Java need to make natural tourist attractions a primary tourist attraction with cultural and artificial tourist attractions as supporting tourist attractions, and prepare their communities for post-pandemic destination governance. This is to realize safe travel for tourists is a step to restore tourist visits in West Java